2020
DOI: 10.1111/gcbb.12665
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon increased by twice the amount of biochar carbon applied after 6 years: Field evidence of negative priming

Abstract: Applying biochar to agricultural soils has been proposed as a means of sequestering carbon (C) while simultaneously enhancing soil health and agricultural sustainability. However, our understanding of the long‐term effects of biochar and annual versus perennial cropping systems and their interactions on soil properties under field conditions is limited. We quantified changes in soil C concentration and stocks, and other soil properties 6 years after biochar applications to corn (Zea mays L.) and dedicated bioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 45 publications
3
55
1
Order By: Relevance
“…The lack of significant differences between either stover removal treatments or tillage systems in this study may be partially explained by high variability in all the plots, as every treatment had coefficients of variation exceeding 42% (error bars not shown in Figure 1 to improve readability). The only consistent response was observed in BC in 2010, and the lower fluxes in this system‐year under both moderate and high stover removal may be partially explained by the potential of biochar to have a negative priming effect on the mineralization of soil C (Blanco‐Canqui et al, 2020), such that the elevated CO 2 fluxes are caused predominantly by the increased residue inputs; however, this effect did not persist in 2011 or 2012.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The lack of significant differences between either stover removal treatments or tillage systems in this study may be partially explained by high variability in all the plots, as every treatment had coefficients of variation exceeding 42% (error bars not shown in Figure 1 to improve readability). The only consistent response was observed in BC in 2010, and the lower fluxes in this system‐year under both moderate and high stover removal may be partially explained by the potential of biochar to have a negative priming effect on the mineralization of soil C (Blanco‐Canqui et al, 2020), such that the elevated CO 2 fluxes are caused predominantly by the increased residue inputs; however, this effect did not persist in 2011 or 2012.…”
Section: Discussionmentioning
confidence: 71%
“…Biochar applications typically cause an initial pulse of CO 2 emissions (Jones et al., 2011), which is due to the combined effects of tillage used to incorporate the biochar, the hydrolysis of carbonates, and the mineralization of labile organic compounds that are added with the biochar (Fidel, Laird, & Parkin, 2017). The long‐term effects of biochar applications on soil respiration are less consistent, as biochar may either enhance mineralization of biogenic soil organic matter (positive priming) or reduce the rate of biogenic SOC mineralization (negative priming) and enhance stabilization of C added to soils with crop reside inputs (Blanco‐Canqui, Laird, Heaton, Rathke, & Acharya, 2020; Chang et al., 2016; Rogovska et al., 2016). Thus, interactions between biochar applications and stover removal and their impact on soil CO 2 fluxes require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study by Blanco‐Canqui et al. (2020) found more than six‐fold higher C accumulation under biochar‐amendment than the non‐amended plots and attributed this to the negative priming effects of biochar on SOC.…”
Section: Discussionmentioning
confidence: 79%
“…While most biochar studies reporting negative priming effects are short term and from laboratory settings (Maestrini et al, 2015), the few emerging field studies indicate significant priming effects of biochar. A field study on a US Midwestern silty clay loam soil found that woody biochar applied at 9.3 Mg ha −1 (63% C) to no‐till corn and dedicated bioenergy crops increased soil C stock twice (14 Mg soil C ha −1 ) the amount of C added with biochar (7 Mg biochar C ha −1 ) compared to no biochar application after 6 years (Blanco‐Canqui et al, 2020). Another field study reported that biochar had a positive priming when applied at 30 Mg ha −1 to a wheat–corn rotation but negative when applied at 60 and 90 Mg ha −1 after 8 years (Sun et al, 2020).…”
Section: Carbon Sequestrationmentioning
confidence: 99%